Adaptive Open Innovation - Solution Approach and Tool Support - Huber, Sebastian; Schott, Peter; Lederer, Matthias (Proceedings of the S-BPM ONE '15, 2015)
The production of valuable and potentially successful products and services according to the prevailing approach of traditional Innovation Management often fails. However, companies constantly face the challenge to develop and maintain their competitive advantage in an increasing competitive international environment. The paradigm of Open Innovation addresses this challenge fostering cross-border collaboration, integrating both upstream and downstream partners alongside the value chain. Since especially the integrative tasks incorporate individual, knowledge-intensive, and weakly-structured processes, new approaches to support people in open innovation projects need to be considered. Adaptive Case Management is specifically designed to manage unpredictable work and to support knowledge workers. From both, a conceptual and technological perspective it is outlined how knowledge workers in the field of open innovation can be supported across company boundaries. This approach is evaluated based on a software prototype and findings on usability as well as acceptance are depicte
WiSo2-Import:2015-10-02:636

A Maturity Model to Organize the Multidimensionality of Digitalization in Smart Factories - Schott, Peter; Lederer, Matthias; Niedermaier, Sina; Bodendorf, Freimut; Hafner, Matthias (Handbook of Research on Applied Optimization Methodologies in Manufacturing Systems, 2017)
Smart Factory concepts describe fully networked, autonomous factories and form an essential part of flexible, but still highly efficient production systems. The requirements for the further development of existing production environments towards a Smart Factory are multidimensional and vastly complex. Many companies therefore fail in the structured realization of a holistic Smart Factory concept. They either focus one dimension of the challenge or merely address the maximum penetration of powerful technologies. This chapter addresses this issue and describes a systematic development path towards a Smart Factory by means of a domain specific maturity model. Based on the analysis of existing maturity models, requirements are derived which must be considered when realizing a Smart Factory. In total, 20 design fields (e.g., degree of intelligence, communication protocols, human-machine-interface and IT security) and respective detail descriptions result from this research. They holistically structure the relevant fields of action to pursue a Smart Factor
Keywords: Complexity; Smart Factory; Automation Pyramid; Smart Objects; Industry 4.0; Maturity Model; Cyber-Physical Systems

Applying the Strategy-oriented Business Process Modeling to S-BPM - Lederer, Matthias; Kurz, Matthias; Lembcke, Ulrike (Communications in Computer and Information Science Volume 422: S-BPM ONE Application Studies and Work in Progress, 2014)
WiSo2-Import:2015-10-06:610

Are Instructions via E-Mail suitable? How to Choose an Effective Communication Medium after Changes in IT-enabled Workflows - Lederer, Matthias; Missal, Felix (Proceedings of the International Conference Information Systems Post-Implementation and Change Management 2015, 2015)
WiSo2-Import:2015-10-02:649

Balancing Customer Satisfaction and Complexity: An Indicator-based Approach with Application in the Automotive Industry - Schott, Peter; Lederer, Matthias; Zwerina, Jan (Proceedings of the 2015 Annual SRII Global Conference, 2015)
WiSo2-Import:2015-10-02:657

BPMS 2.0: Übertragung der geleiteten Selbstorganisation auf die Prozessautomatisierung - Kurz, Matthias; Lederer, Matthias; Billing, Gunnar; Hettling, Karl; von Jouanne-Diedrich, Holger (IM : die Fachzeitschrift für Information Management und Consulting, 2011)
WiSo2-Import:2015-09-25:634

BPM-Tools im Überfluss – Wie strategische Kriterien die Auswahl des richtigen IT-Werkzeugs beeinflussen: Einführung, Praxisreflexion, Perspektiven - Lederer, Matthias; Huber, Sebastian; Bodendorf, Freimut (Schulisches Prozessmanagement - Einführung, Praxisreflexion, Perspektiven, 2015)

Business Process Deployment Scorecard: Managing Process Changes Transparently - Lederer, Matthias; Huber, Sebastian; Zellner, Christian (Proceedings of the International Conference Information Systems Post-Implementation and Change Management 2013, 2013)
The increasing frequency of changes in corporate environments results in the necessity of according business process adaptions. Since the introduction of new processes is usually accompanied by respective changes within the organization and process environment, process managers are frequently confronted with a great number of challenges. The deployment of processes, including all crucial tasks for the implementation of new and/ or adapted business processes, becomes an increasingly relevant phase in the BPM lifecycle. Currently, research and guidelines for practitioners predominantly collect those challenges and list isolated best practices for business process deployment projects. Thus a comprehensive framework structured like a scorecard is needed in which measures for successful deployment can be organized in verifiable areas. Based on a systematic literature review and an analysis deployment projects, this work presents a classification of challenge areas (e.g., interfaces, corporate culture) which are particularly critical for process deployment. Afterwards, these areas are used for an organizational framework, which allows process practitioners to plan, execute, and control deployment projects in a holistic and balanced way. This Deployment Scorecard has been presented to experienced practitioners and tested against the background of three real deployment projects.
WiSo2-Import:2015-10-02:593
Keywords: Business process deployment; Business process transparency management; Deployment scorecard; Process implementation

Business Process Transparency Management: An Approach for Middle Managers to Aligning Processes, Teams and IT-Tools to Corporate Strategy - Lederer, Matthias (S-BPM ONE 2014, 2014)
WiSo2-Import:2015-10-05:609

Business Process Transparency Management: An Approach to Aligning Business Processes and Corporate Strategy - Lederer, Matthias (Proceedings of the International Conference Information Systems Post-Implementation and Change Management 2013, 2013)
Business process management practitioners often face the challenge of translating the long-term business strategy from the top management into operational BPM implications for teams and information systems. At the same time, the top management wants a founded bottom-up control of BPM activities concerning their contribution to the corporate strategy. Business Process Transparency Management (BPTM) describes a framework in progress which aims to make a contribution to this business problem by providing guidelines, new methods, and best practices for strategy implementation and controlling.
WiSo2-Import:2015-10-02:594
Keywords: BPTM; Business process management; Business Process Transparency Management; Strategy alignment

Business Process Transparency Management Modeling Notation: Ein Kommunikationsansatz für mittlere Manager mit Evaluation in der Automobilbranche - Lederer, Matthias; Lembcke, Ulrike (2013)
WiSo2-Import:2015-10-07:604

Business Process Transparency Management: Operationalisierung der Sichtbarkeit strategischer Zielsetzungen im taktischen Geschäftsprozessmanagement - Lederer, Matthias (2016)

Case-based reasoning for complexity management in Industry 4.0 - Schott, Peter; Lederer, Matthias; Eigner, Isabella; Bodendorf, Freimut (Journal of Manufacturing Technology Management, 2020)
Purpose: Increasingly, dynamic market environments lead to growing complexity in manufacturing and pose a severe threat for the competitiveness of manufacturing companies. Systematic guidance to manage this complexity, especially in the context of Industry 4.0 and the therewith rising trends such as digitalization and data-driven production optimization, is lacking. To address this deficit a case-based reasoning (CBR) system for providing knowledge about managing complexity in Industry 4.0 is presented. Design/methodology/approach: First, the explicit knowledge representation for managing complexity in IT-based manufacturing is introduced. Second, the CBR process step to retrieve knowledge from an artificially composed case base with in total 70 cases of data-based complexity management in the context of Industry 4.0 is set out. Third, knowledge transfer alongside several maturity levels of information technology capabilities of manufacturing systems for reuse in new problem scenarios is introduced. Findings: The paper comprises the conceptual approach for designing a CBR system to support data-based complexity management in manufacturing systems. Furthermore, the appropriateness of the CBR system to provide applicable knowledge for reducing and managing complexity in corporate practice is shown. Research limitations/implications: The presented research results are evaluated in the course of an embedded single case study and may therefore lack generalizability. Future research to test and enhance the appropriateness of the developed CBR system will strengthen the research contribution. Originality/value: The paper provides a novel approach to systematically support knowledge transfer for data-based complexity management by transferring the well-known and established methodology of CBR to the rising application domain of manufacturing systems in the context of Industry 4.0.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Complexity; Knowledge based systems; Manufacturing systems

Connectivity, Simplification, and Performance Measurement: Guidelines for Business Process Strategists in Re-Engineering Projects - Lederer, Matthias; Huber, Sebastian (IADIS International Journal on Computer Science and Information Systems, 2014)
WiSo2-Import:2015-09-25:629

Der mittlere Prozessmanager: Aufgaben der Transferfunktion - Lederer, Matthias; Butz, Felix; Bodendorf, Freimut (2015)
WiSo2-Import:2015-10-07:642

Die Strategie-Prozess-Matrix in der Praxis: Evaluation einer neuen Modellierungsnotation - Lederer, Matthias; Aydin, Hacer; Bodendorf, Freimut (2015)
WiSo2-Import:2015-10-07:644

Ein Empfehlungssystem für Prozessoptimierungen im Product Lifecycle Management als Ideengeber und Entscheidungshilfe für mittlere Manager - Lederer, Matthias; Gerber, Stefanie (Proceedings of the 12th International Conference on Wirtschaftsinformatik, 2015)
Prozessverantwortliche mittlere Manager stehen vielfach vor der Herausforderung die ihnen vorgegebenen strategischen Zielstellungen für Geschäftsprozesse in konkrete Optimierungsmaßnahmen zu überführen. Der Beitrag entwickelt hierfür stufenweise ein inhaltliches Empfehlungssystem, mit dem Manager in der Prozessgruppe Product Lifecycle Management (PLM) für ihren Anwendungsfall passende Maßnahmen identifizieren können. Hierfür werden typische Unternehmensziele zunächst für die sequentiellen PLM-Phasen kaskadiert. Eine anschließende Matrixzuordnung von State of the Art-Optimierungsmaßnahmen stellt eine inhaltliche Verbindung von Zielen und Maßnahmen mit Kontrollindikatoren her. Mithilfe eines webbasierten Prototyps wird das Empfehlungssystem in einer Fallstudie verprob
WiSo2-Import:2015-10-02:637

Ein mathematisches Ressourcenverteilungsmodell zur strategischen Prozessoptimierung - Lederer, Matthias; Mrosek, Alexander; Bodendorf, Freimut (2015)

Enhancing Process Compliance in Complex Product Developments – Insights from an International Manufacturer - Schott, Peter; Lederer, Matthias; Huber, Sebastian; Keppler, Alexander (Proceedings of the S-BPM ONE '15, 2015)
Poor process compliance oftentimes leads to insufficient fulfillment of strategic goals. To prevent this, adequate initiatives to achieve process compliance and consequently to achieve corporate objectives need to be taken. In this context, the product development represents a significant core process to achieve strategic goals for manufacturing companies. Using the example of an international manufacturer, this contribution describes the derivation of effective actions to increase compliance with the product development process by using S-BPM models. The relevant stakeholders as well as the role specific tasks and responsibilities are identified assessing interactions and behaviors applying Subject Oriented modeling notations. Based on this basic information, we conduct semi-structured interviews with relevant stakeholders to identify the problem areas where process users need support. Moreover, we conclude implications to increase process compliance and show how to translate these implications into actual support content such as templates and checklist
WiSo2-Import:2015-10-02:638

Geschäftsprozesse auf Kurs halten: Ein Framework zum strategischen Prozess-Controlling mit einer Fallstudie aus der industriellen Produktentwicklung - Lederer, Matthias; Schott, Peter; Keppler, Alexander; Bodendorf, Freimut (2014)
WiSo2-Import:2015-10-07:631

Increasing Strategy-Achievement in Business Processes and Information Systems using an Objective-based Optimization Approach - Lederer, Matthias; Huber, Sebastian; Kocak, Ilknur (Proceedings of the International Conference Information Systems Post-Implementation and Change Management 2014, 2014)
Business processes should be aligned to corporate strategy. However, especially post-implemented business processes tend to an inefficient implementation of business objectives. Process managers are facing the challenge how to optimize established workflows in organizations based on strategic objectives. This contribution proposes a new modeling approach, which links business goals with flow objects of business processes in a Strategy Process Matrix. Three basic optimization rules are developed, which lead process owners to actual corrective actions to increase the strategy achievement of processes. This transparent optimization approach is used in the case study of customer support processes of a manufacturing company from Switzerland and shows the added value of the optimization approach.
WiSo2-Import:2015-10-02:611
Keywords: Business process optimization; Business process redesign; Process transparency management; Strategy process matrix

IT-basiertes Transparenzmanagement für die Analyse von Geschäftsprozessen - Lederer, Matthias; Schott, Peter (2012)
WiSo2-Import:2015-10-07:578

IT-enabled Adaptive Open Innovation - Huber, Sebastian; Schott, Peter; Lederer, Matthias (ECIS 2015 Completed Research Papers, 2015)
Lacking efficiency and transparency regarding cross-company collaboration in the field of in-novation management often leads to cost intensive and unsuccessful products and services. This is due to the fact that traditional Innovation Management approaches fail in terms of coping with emerging requirements in Open Innovation projects, e.g. the vertical and horizontal inte-gration of strategic partners within and across the company’s value network. However, compa-nies are forced to maintain their competitive advantage through a constant and sustainable de-velopment of their product and service portfolio. In this context, knowledge workers play an im-portant role in the collaborative advancement of innovative product and service ideas. For that reason, knowledge workers need systematic support regarding both methodological and opera-tional challenges in the field of Open Innovation. The concept of Adaptive Case Management emerged from the necessity to support knowledge workers in unpredictable working environ-ments. Therefore, this contribution shows, both from a conceptual and technological point of view, how knowledge workers can be supported in cross-border innovation projects. The ap-proach is evaluated using an Adaptive Case Management software prototype and the findings on concept acceptance and software usability are presente
WiSo2-Import:2015-10-02:656

IT-enabled Collaborative Case Management: Principles and Tools - Huber, Sebastian; Lederer, Matthias; Bodendorf, Freimut (Proceedings of the 2014 International Conference on Collaboration Technologies and Systems, 2014)
Adaptive Case Management (ACM) is a new paradigm to support dynamic business processes that are mainly unpredictable and knowledge-intensive. However, fundamental knowledge about this approach is currently scattered across a series of collective volumes and web blogs that tend to focus on isolated aspects or domain-specific challenges and solution approaches. As the ongoing discussion still lacks comprehensive theoretical literature, principles are driven mostly by individual circumstances and common ideas are not transparent. Therefore, the paper at hand provides a structured, domain-independent overview about the common principles in ACM and derives a set of distinct challenges in order to contribute to the general understanding of this paradigm. This work consolidates existing literature and subsequently focuses on the implied role of collaboration. To complement the theoretical discussion, a reference implementation demonstrates the key concepts. © 2014 IEEE.
WiSo2-Import:2015-10-02:612
Keywords: Adaptive Case Management; Business Process Management; Computer-supported Cooperative Work

It is all About the Interface: Factors which Drive Process Interface Criticality in Organizations - Lederer, Matthias; Heider, Laura (Proceedings of the 42nd Euromicro Conference on Software Engineering and Advanced Applications, 2016)

Konzept und Umsetzung eines Prozessportals für mittlere Prozessmanager - Lederer, Matthias; Kupfer, Christopher; Leitermann, Alexander; Hofmann, Tobias; Schaffert, Christopher; Roth, Fabian; Bodendorf, Freimut (2016)

Leaving the Happy Path: Handling Exceptions in Business Processes - Kurz, Matthias; Lederer, Matthias; Huber, Sebastian (Proceedings of the International Conference on Information Systems 2013, 2013)
WiSo2-Import:2015-10-02:582

Leveraging CMMN for ACM: Examining the applicability of a new OMG standard for adaptive case management - Kurz, Matthias; Schmidt, Werner; Fleischmann, Albert; Lederer, Matthias (Proceedings of the S-BPM ONE '15, 2015)
Adaptive case management (ACM) is an increasingly popular approach for supporting knowledge-intensive business processes. Being a new approach, it still lacks a similar degree of standardization as the more established business process management (BPM) approaches. This paper introduces the new Case Management and Model and Notation (CMMN) standard. Based on a set of ACM requirements, the applicability of CMMN for modeling ACM cases is examined thoroughly and extensions improving the ACM support of CMMN are propose
WiSo2-Import:2015-10-02:635

Lösungswissen Industrie 4.0: Eine reifegradorientierte Beschreibungsvorschrift technischer Lösungsprinzipien zur Komplexitätsbeherrschung in bestehenden Produktionssystemen - Schott, Peter; Lederer, Matthias; Khomut, Michael; Ahlers, Sven; Bock, Matthias; Bodendorf, Freimut (2017)

Making strategy work: A comprehensive analysis of methods for aligning strategy and business processes - Lederer, Matthias; Kurz, Matthias; Lazarov, Pavlin (International Journal of Business Performance Management, 2017)
A key objective of strategy management is ensuring the implementation of strategies in the day-to-day operational business processes of enterprises. For this purpose, researchers and practitioners developed an enormous body of methods for strategy management. However, the tremendous variety of strategy management methods makes it difficult to choose the most appropriate methods for a given challenge. In order to learn from field studies and to provide guidance for practitioners and researchers, this paper provides a dataset of the 50 methods from a body of 100 case studies focusing on strategy design and implementation in the field of business process management. Based on this dataset, commonly utilised methods, common challenges, typical objectives and the role of the management levels are examined. Researchers may use this freely available dataset as a foundation for their own further research.<br
Keywords: balanced scorecard; BSC; business process management; BPM; strategy definition; strategy implementation; strategy-process alignment; strategy management

Managing Complexity in Adaptive Case Management - Huber, Sebastian; Hauptmann, Adrian; Lederer, Matthias; Kurz, Matthias (S-BPM ONE Running Solutions: 5th International Conference S-BPM ONE 2013 Proceedings, Deggendorf, Germany, 2013)
The success of knowledge work represents one of the most important assets for businesses to date, and managers across all industries are searching for new ways to increase the productivity in this domain. Since traditional approaches, such as Business Process Management do not provide the suitable context to support knowledge intensive workflows, the recent trend of Adaptive Case Management has set out to address this issue by providing a framework that supports the required flexibility and enables an agile and dynamic environment. However, fundamental knowledge about this approach is currently scattered across a series of collective volumes and web blogs that tend to focus on isolated aspects or domain-specific challenges and solution approaches. As the ongoing discussion still lacks comprehensive theoretical literature, principles are driven mostly by individual circumstances, and common ideas are not transparent. The goal of this research effort is to provide a structured, domain-independent overview about the common principles in ACM and derive a set of distinct challenges in order to contribute to the general understanding of this paradigm. This work therefore discusses and consolidates existing literature, and subsequently focuses on the role of complexity in knowledge work to provide a foundation for the resulting challenge definitions. To complement the theoretical discussion, the final section of this paper provides a series of selected solution approaches that effectively support knowledge-intensive workflows. © 2013 Springer-Verlag.
WiSo2-Import:2015-10-05:579
Keywords: Adaptive Case Management; Business Process Management; Complexity Challenges

Managing Consistency of E-Service Requirements for Business Processes - Lederer, Matthias; Schott, Peter (Proceedings of the 2015 Annual SRII Global Conference, 2015)
WiSo2-Import:2015-10-02:658

Picking with Impact - Best Practices for the Quality Improvement and Cost Minimizing of Consignment in the Logistics of an International Manufacturer - Lederer, Matthias; Niedermeier, Ferdinand; Hoppe, Jan (Handbook of Research on Global Supply Chain Management, 2015)
WiSo2-Import:2015-10-06:647

Planning for the Unexpected: Exception Handling and BPM - Kurz, Matthias; Fleischmann, Albert; Lederer, Matthias; Huber, Sebastian (S-BPM ONE Running Solutions: 5th International Conference S-BPM ONE 2013 Proceedings, 2013)
Traditional S-BPM successfully focuses on standardized business processes which are performed according to a fixed predefined process model. Yet a substantial share of business processes is difficult to predict with exceptions to the core processes occurring frequently. This contribution proposes to explicitly consider exceptions and handle them according to their degree of standardized behavior. A methodology comprising three main components provides guidance for this new perspective on exceptions: (1) a classification details the types of exceptions that are encountered in real-world S-BPM projects. (2) An approach inspired by the exception handling mechanisms in software engineering advises methods and tools for handling the exception types and suggests a corresponding escalation mechanism. Both the classification and the procedure model are validated by ten domain experts. (3) The S-BPM notation is extended in order to effectively leverage the proposed approach. © 2013 Springer-Verlag.
WiSo2-Import:2015-10-05:580
Keywords: Abstract State Machine; Adaptive Case Management; Event driven business process management; Exception Handling; Happy Path

Process2IT. An Approach for the Systematic Selection of BPM Tools - Kurz, Matthias; Brügmann, Hinnerk; Lederer, Matthias (2011)
WiSo2-Import:2015-10-06:495

Revitalizing established Industrial Companies: State of the Art and Success Principles of Digital Corporate Incubators. - Hille, Matthias; Lederer, Matthias; Forster, Dominik (14. Internationale Tagung Wirtschaftsinformatik, 2019)
In order to compete with radical digital ideas, more and more large companies are founding corporate incubators. These small and agile companies are designed to accelerate disruptive innovation and transfer it to the parent company. However, it is obvious that the design and work in these newly established units are often efficient and the return of ideas cannot be effectively realized. This paper has collected a list of 131, partly non-public, incubators and evaluated them according to classic design parameters for companies (e.g., location, industry, etc.). In addition, success factors for digital corporate incubators (such as the design of the innovation process) were collected for deriving success principles.<br
Keywords: Corporate incubators; innovation management; start-up management; innovation lab; new business development

Strategic Business Process Analysis: A Procedure Model to Align Business Strategy with Business Process Analysis Methods - Lederer, Matthias; Schott, Peter; Huber, Sebastian; Kurz, Matthias (S-BPM ONE Running Solutions: 5th International Conference S-BPM ONE 2013 Proceedings, 2013)
In literature and business practice, implementing the business strategy and analyzing business processes is often addressed separately although business processes are regarded as a competitive key resource. In many businesses, it is unclear which systematic approach is most appropriate to identify process analysis methods which support the achievement of strategic objectives best. This contribution proposes an association model for the systematic combination of corporate strategy and business process analysis methods: First, it describes how a corporate strategy can be formalized. Then, a system is designed that rates known process analysis methods according to their support of the process strategy. Users of the model only have to rate the importance of strategy classes on a numerical scale. In order to validate the model, it has been tested during expert interviews and by applying it for real processes from different companies. © 2013 Springer-Verlag.
WiSo2-Import:2015-10-05:581
Keywords: Business Process Strategy; Process Analysis Methods; Strategy Analysis

Strategic Business Process Modeling: Visualization and IT-enabled Support System - Lederer, Matthias (Proceedings of the 2nd International Workshop on Process Modelling Support Systems, 2015)
WiSo2-Import:2015-10-02:648

Subject-oriented Adaptive Case Management: Extending Subject-oriented Business Process Management to Knowledge-intensive Cross-enterprise Business Processes - Kurz, Matthias; Lederer, Matthias (Lecture Notes in Business Information Processing Volume 170: S-BPM ONE - Scientific Research, 2014)
WiSo2-Import:2015-10-05:608

Subject-Oriented Business Processes meet Strategic Management: Two Case Studies from the Manufacturing Industry - Lederer, Matthias; Schott, Peter; Kurz, Matthias (S-BPM in the Wild, 2015)
Successful companies use business processes for the transfer of long-term strategies in operational workflows. The modeling approach presented in this chapter shows how strategic objectives of a company can be combined with the S-BPM modeling notation. The new modeling approach is used in two case studies. First, redesign rules for the strategic optimization of workflow models are demonstrated in the case of the customer support processes of an international enterprise. A second case study introduces a company-wide monitoring system through the example of the product development process of a multinational company from German
WiSo2-Import:2015-10-06:628

The BSC Cookbook: Vol. 1 - Ingredients for a Successful Balanced Scorecard - Lederer, Matthias; Raake, Dieter; Kurz, Matthias (I2PM, 2014)
WiSo2-Import:2015-10-05:633

Usage and Suitability of Methods for Strategic Business Process Initiatives: A Multi Case Study Research - Lederer, Matthias; Kurz, Matthias; Lazarov, Pavlin (International Journal of Productivity Management and Assessment Technologies, 2017)

Using a Strategy-oriented Business Process Modeling Notation for a Transparent Company-wide Business Control System - Lederer, Matthias; Schott, Peter; Keppler, Alexander (International Journal of Decision Support Systems, 2015)
Business processes should be aligned to the corporate strategy and relevant BPM decisions should be made in accordance with strategic objectives. However, there is still no established standard notation for explicitly designing strategic targets in process models. While middle and lower managers need an approach which helps to decide on corrective actions to fulfil business needs, top managers require a systematic approach to control strategic targets based on process instances. This paper proposes an approach on how strategies and business objectives can be integrated in business process models. The described notation of a strategy process matrix is then used to create an enterprise-wide control system for stakeholders on different hierarchical levels of an organisation. The added value of the system is outlined in a field test in a German manufacturing compan
WiSo2-Import:2015-09-25:626

Vom Prozessmodell zum Lastenheft: Ein konzeptioneller Business-IT-Alignment-Ansatz mit Anwendung im CRM - Lederer, Matthias; Schott, Peter; Bodendorf, Freimut (2015)
WiSo2-Import:2015-10-07:645

What are Middle Managers expecting from Strategic Tools? A Collection and Analysis of State of the Art Instruments - Hauck, Vera; Lederer, Matthias; Bodendorf, Freimut (Global Business and Economics Review, 2017)
Many strategic tools are available for process managers to develop, document and communicate their long-term business planning. However, middle managers are often facing the challenge to successfully understand and communicate a company's strategy because not always the most suitable instrument for a specific situation is chosen. In the majority of cases, the balanced scorecard is utilised for the strategy documentation and control although a lot more tools are available. This paper provides a collection as well as an in-depth analysis of currently known and widely used strategy instruments. An extensive list of requirements towards strategic tools is used to evaluate how reasonable the usage of these state of the art tools is in process management. The resulting recommendation system identifies the strategy map as well as the success resource deployment as also highly relevant instruments for middle process managers. Moreover, the developed generic system can be used by middle managers to identify the most suitable tool for their purpose and business situation.<br
Keywords: strategic tools; strategy instruments; strategy documentation; middle manager; process management; business process transparency management

When Process Managers act as Requirements Engineers: A Template-based Proposal using Workflow Models to derive Innovative IT Requirements - Lederer, Matthias; Schott, Peter; Kurz, Matthias (Proceedings of the S-BPM ONE '15, 2015)
WiSo2-Import:2015-10-07:643